Excited and exotic charmonium, Ds and D meson spectra for two light quark masses from lattice QCD - RYAN, SINEAD; PEARDON, MICHAEL (My University, 2016)
We present highly-excited charmonium, D s and D meson spectra from dy- namical lattice QCD calculations with light quarks corresponding to M 240 MeV and compare these to previous results with M 400 MeV. Utilising the distillation framework, large bases of carefully constructed interpolating operators and a variational procedure, we extract and reliably identify the continuum spin of an extensive set of excited mesons. These include states with exotic quantum numbers which, along with a number with non- exotic quantum numbers, we identify as having excited gluonic degrees of freedom and interpret as hybrid mesons. Comparing the spectra at the two di erent M , we nd only a mild light-quark mass dependence and no change in the overall pattern of states.
PUBLISHED
Export Date: 6 January 2017
Keywords: highly-excited charmonium; highly-excited charmonium